Values of travel time in the AKTA project - Jovicic, Goran; Nielsen, Otto Anker (Proceedings from the Annual Transport Conference at Aalborg University, 2003)
AKTA (http://www.akta-kbh.dk) is a research study under the EU-project PROGRESS (www.progress-project.org), which is part of the EU’s 5th framework programme named ‘The Growth Programme on Sustainable Mobility and Intermodality’. The programme supports several studies related to road pricing and similar subjects in traffic planning. PROGRESS includes eight European cities that research in different types of tolls. These cities are Bristol and Edinburgh (UK), Genoa and Rom (Italy), Helsinki (Finland), Trondheim (Norway), Gothenburg (Sweden) and Copenhagen. AKTA’s deadline is in autumn 2003, after a 31⁄2 year long project period. The budget in the study is about DKK 13.5 million. More about the project itself can be found in Nielsen & Herslund, 2002 and Nielsen & Jovicic, 2003. The aim of the paper is to present the obtained values of travel time (VOT) in the AKTA SP project. Basis for the VOT is Stated Preference (SP) data, which has been collected specifically for the purposes of the project. Three main effects are described in the paper: methodological effect; respondents’ perception of VOT based on presented travel costs versus travel distances in the SP experiments, theoretical effect; differences in the obtained VOT based on ordinary MNL models and Error Component (EC) models, and income effect; differences in the obtained VOT with and without the income effect. Section two describes AKTA’s SP survey. The following section depicts some important theoretical aspects of the VOT in logit models. Section four is the main part of the paper where the modelling work is presented. Concluding discussion and remarks are given in the last section.